Civil society organizations in the informal settlements of Buenos Aires : service providers and forces for change - Mitchell, Ann Elizabeth (2016)
Fil: Mitchell, Ann. Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina Argentina